Pengaruh Absensi Sidik Jari (Fingerprint) Terhadap Disiplin Aparatur Sipil Negara pada Dinas Pendidikan dan Kebudayaan Kota Lhokseumawe - Ramayani Ramayani; Ferizaldi Ferizaldi (Asia-Pacific Journal of Public Policy, 2021)
One of the tasks that need to be considered in enforcing a disciplined and conducive work situation in a government agency is the frequency of the presence of State Civil Apparatus. The frequency of attendance is now controlled through the FingerPrint Attendance system. This study aims to explore the effect of Fingerprint Attendance on the Discipline of the State Civil Apparatus at the Education and Culture Office of Lhokseumawe City. The research method employed was quantitative with a saturated sampling technique (census) and the sample participants were all respondents who are all State Civil Apparatuses within the Education and Culture Office of Lhokseumawe City. The data analysis method used was simple linear regression analysis. The results of this study indicated that Fingerprint Attendance has a positive and significant effect on the discipline of the State Civil Apparatus, this is evidenced by the results of the t-test (partial test) obtained by comparing the significant value in the t-test table with a significance level of 0.05 obtained (0.000 < 0.05); the result was that the H1 was accepted. Based on the results of the coefficient of determination test (R2), the coefficient of determination (R2) is 0.280 (28%).